Realizing Biring Ere Village as an Agro-Industry Based Tourism Village - Suardi Bakri; Ahmad Hanafie; Eka Lestari Aryanti; Mardiatul Jannah; Kisman Awaluddin Arsyad; Qurniasty (LPPM Universitas Muhammadiyah Tasikmalaya, 2024)
Advancing and prospering village communities is the main goal of every village government, including Biring Ere Village which is located around the Semen Tonasa industrial area in Bungoro District, Pangkep Regency, South Sulawesi by utilizing resources. The vision of Biring Ere Village is to realize Biring Ere Village as an agroindustry-based integrated tourism village and to realize this vision, the village government collaborates with various parties, including Universitas Islam Makassar. The general aim of this activity is to create independence, comfort and welfare for the community througha synergy of capability-based expertise and village government policies and community potential. The activity was carried out in Biring Ere Village, Bungoro District, Pangkep Regency, South Sulawesi for 6 months, April to September 2024. The target group for this activity was the productive economic group,namely the Women Farmers Group (KWT) and the Family Income Increase Unit (UP2K). The results ofthe service show that the method of producing farming and processing the results carried out by the target group has changed from a simple farming process to a farming based on smart farming. With theintroduction of technology in the form of smart farming, KWT can produce efficiently and effectively, increasing the volume and variety of commodities produced. Meanwhile, for UP2K the technology introduced is results processing technology. So that the processing of agricultural products meets market standards.